ANALISIS PENERAPAN PERATURAN DAERAH NOMOR 8 TAHUN 2012 TENTANG RETRIBUSI PARKIR TEPI JALAN UMUM DI KOTA SURABAYA - Juniasari, Putu Ayu Mentari (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to know how the practice of regional regulations (No 8/2012) in Surabaya City about public roads service parking?s retribution for motorcycle as the regional revenue of Surabaya City. The method used is a qualitative descriptive. This method trying to describe about the facts between in the field and in the regulation. The result of this research can be known by the irrelevancy of the regional regulation number 8 year 2012?s Surabaya City with the reality.Keywords: regional regulation, irrelevancy, motorcycle, public roads service parking?s retribution.